2020
DOI: 10.1007/s40261-020-00927-1
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Systematic Review of the Therapeutic Role of Hydroxychloroquine in Coronavirus Disease-19 (COVID-19)

Abstract: Background and ObjectiveThe world is currently experiencing the Coronavirus Disease-19 (COVID-19) pandemic. There is no approved drug for the definitive treatment of the disease. Various drugs are being tried for the treatment of COVID-19, including hydroxychloroquine (HCQ). This study was performed to systematically review the therapeutic role of HCQ in COVID-19 from the available literature. Methods PubMed, Embase, ClinicalTrials.gov, ICTRP (WHO), Cochrane Library databases, and two pre-print servers (medRxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 57 publications
5
93
0
7
Order By: Relevance
“…Hydroxychloroquine was largely used in the early period of COVID-19 pandemic owing to its in vitro activity against the virus and relatively safe profile. However, an observational study of 811 patients treated with hydroxychloroquine failed to show any clinical benefit compared with standard of care [38], and a systematic review raised concerns about the quality of published studies [39]. Interim results of the Solidarity Trial showed no significant reduction in mortality of hospitalized COVID-19 patients treated with either hydroxychloroquine or lopinavir/ritonavir compared to standard of care, and these arms of the study were discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloroquine was largely used in the early period of COVID-19 pandemic owing to its in vitro activity against the virus and relatively safe profile. However, an observational study of 811 patients treated with hydroxychloroquine failed to show any clinical benefit compared with standard of care [38], and a systematic review raised concerns about the quality of published studies [39]. Interim results of the Solidarity Trial showed no significant reduction in mortality of hospitalized COVID-19 patients treated with either hydroxychloroquine or lopinavir/ritonavir compared to standard of care, and these arms of the study were discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…However, opposite findings have been reported [30] and the role of HCQ in the development of AKI has still to be fully elucidated, and larger randomized clinical trials are warranted to address this issue. Use of HCQ in COVID-19 patients is largely debated [31].…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloroquine was at the disposal for ICU intensivists at any time because this drug is in stock for chronic disease such as patients with systemic lupus erythematosus. When doubts were raised regarding effectiveness of hydroxychloroquine, this antiviral strategy was replaced by administration of camostat mesylate by mid of March ( 3 , 4 ). The following doses were used: hydroxychloroquine was administered with a loading dose of 400 mg on day 1 followed by 200 mg days 2–5 and camostat mesylate at the maximum dose of 3 × 200 mg daily for 5 days according to information based on a protocol of a larger trial in Denmark (clinical trials reference: NCT04321096).…”
Section: Methodsmentioning
confidence: 99%